Fearism and Racism: Investigating Middle Eastern Refugee Youth’s Lived Experiences in the United States - Kayaalp, Dilek (European Journal of Social Science Education and Research, 2023)
In this study, I explore the social experiences of Middle Eastern refugee youth in the United States. Sixteen young people from Afghanistan, Iran, Iraq, and Syria aged 15 to 31 participated in this research. Hall’s conceptualization of representation, Ahmed’s cultural politics of emotion, Cohen’s moral panic, and Fisher’s fearism proved to be useful theoretical tools to examine refugee youth’s experiences of marginalization and racism. To explore the refugee youths’ lived experiences, I conducted a critical ethnographic inquiry. I conducted my fieldwork (in-depth interviews and participant observations) in Florida, for two years, from 2017 to 2019. The interview data indicate that racist narratives and misrepresentation of refugee youth negatively affect young people’s experiences and social participation. In response, this study suggests continued investigation of the interplay between representation and fearism to decode state discourse and dominant cultural codes to provide alternative forms of social participation for refugee youth.